COMMUNITY MIDWIFERY CARE COMPETENCIES RELATED TO IMPLEMENT OF CARE COMMUNITY - Putriana, Yeyen (Jurnal Penelitian STIKES Kediri, 2012)
One of the measurement on the qualification of higher education is the presence of relevance between the product resulted and the needs of the community as its client.  The purpose of this study was to analyze the relevance (relationship) between the mastery of knowledge competency of community midwifery care and Public Health Sciences. This type of this  research is with cross-sectional approach using proportionate stratified random sampling technique, has been conducted to 40 respondents D-3 midwifery graduates who served as rural midwife and implemented PHN programs in the village. Competence variable and ability to implement PHN programs were measured by questionnaire witha Likert scale of 1−5. Statistical tests using Pearson Correlation. The results of this study showed that the correlation between the mastery of knowledge competency of community midwifery care and Public Health Sciences. The correlation between community Midwifery care skills with the ability to implement PHN was not meaningful and very low, the attitude towards PHN with the ability to implement PHN had a very strong and meaningful correlation p <0.05. The conclusion of this study showed that positive midwives’ attitude toward PHN efforts and midwives’ ability to implement PHN have very strong and meaningful relevance.